Gillûlîm: Rollers, Scarabs in Ezekiel - Adam, Klaus-Peter (The catholic biblical quarterly, 2021)
In keeping with the semantic core of the root גלל , the term גלולים designates“rollers.” Connections with Egypt suggest a more specific use of גלולים in a number of passages of the Hebrew text of Ezekiel. It is a designation of the widely spread iconographic concept of the scarab, with its phenotypes of scarab-shaped and scaraboid stamp seals, heart scarabs, and depictions on reliefs. Heart-shaped amulets alluding to the scarab ideology provide the backdrop of Ezek 14:3. The scarab’s association with the heart replacement in Egyptian mortuary cult shapes the backdrop of Ezek 6:5-6 and 36:25-27.